The Determinants of Attitudes toward Strategic Default on Mortgages - GUISO, LUIGI; SAPIENZA, PAOLA; ZINGALES, LUIGI (Journal of Finance, 2013)
ABSTRACT We use survey data to measure households’ propensity to default on mortgages even if they can afford to pay them (strategic default) when the value of the mortgage exceeds the value of the house. The willingness to default increases in both the absolute and the relative size of the home‐equity shortfall. Our evidence suggests that this willingness is affected by both pecuniary and non‐pecuniary factors, such as views about fairness and morality. We also find that exposure to other people who strategically defaulted increases the propensity to default strategically because it conveys information about the probability of being sued.